A tensile strength of bermuda grass and vetiver grass in terms of root reinforcement ability toward soil slope stabilization - M. N., Noorasyikin; M., Zainab (Penerbit UTHM, 2021)
Nowadays, slope failure is the most frequent phenomena occurring on Earth. The geotechnical engineer always faces a problem especially with shallow failure. Shallow failure which is estimated at depth about 1 to 1.5 meters is still under aware solving problems. There is none a good option to mitigate the slope failure until today. Apart from that, the bioengineering technique which is vegetation cover was usually applied for mitigation of slope failure because of its advantages. Generally, the vegetation mainly stabilizes the slope by mechanical effects through the root matrix system (Chok et al.,2004, Sasan et al., 2009). The soil shear strength is found to increase through the mechanical effects of the vegetation root matrix system where the root acts as reinforcement toward the soil. (Chok et al.,2004, Sasan et al., 2009). In Malaysia environment, Bujang and Sina (2010) stated that the vegetation can potentially provide immediate mechanical shear strength for slope remedial and long-term beneficial effects. This study shall investigate the main factors that influence the vegetation root toward slope failure. An examination on root characteristics and root properties of Bermuda grass and Vetiver grass has been implemented in this study since these grasses were widely applied for slope stabilization in Malaysia.